Antifungal potential of volatile compounds of Actinobacteria against a selection of fungal phytopathogens - Seiter, Jana (Jihočeská univerzita, 2022)
In the present study, the antifungal potential of volatile compounds, produced by a selection of Actinobacteria, was tested against several fungal plant pathogens, belonging to the genus of Fusarium and Geotrichum. Therefore in vitro experiments were performed, in which two-compartment Petri dishes were used. This was followed by an evaluation of the potential suitability of the volatile producing bacteria for their possible application in biological control of the tested pathogens.
Antifungal potential of volatile compounds of Actinobacteria against a selection of fungal phytopathogens
Keywords: Actinobacteria; antifungal volatiles; biocontrol; fungal phytopathogens; Actinobacteria; antifungal volatiles; biocontrol; fungal phytopathogens